PENERAPAN IPTEK UNTUK PEMBANGUNAN GREEN HOUSE PEMBIBITAN PADA PROGRAM URBAN FARMING DI RT 06 RW 13 JALAN BUKIT CEMARA INDAH XI KELURAHAN METESEH KECAMATAN TEMBALANG SEMARANG: PENERAPAN IPTEK UNTUK PEMBANGUNAN GREEN HOUSE PEMBIBITAN PADA PROGRAM URBAN FARMING DI RT 06 RW 13 JALAN BUKIT CEMARA INDAH XI KELURAHAN METESEH KECAMATAN TEMBALANG SEMARANG - Buana, Lalu Yahya Surya; Praharseno, Fikri; Suwarto; Lestari, Nor Puji; Ariyanto, Arief Subakti; Sulaiman, Sriwahyuningsih; Suparman; Wahjoedi; Parhadi; Devilito, Rio (Bangun Rekaprima, 2025)
Urban farming is an effort to maintain resilience in the capital city of Central Java. The Semarang City Government continues to be committed to improving the quality of regional development with benchmarks from aspects of development achievement, quality aspects, document preparation aspects, and innovation aspects. In 2023, the Semarang City Government will carry out program innovations such as the Food Startup Challenge, Urban farming Corner, Rumah Gizi Pelangi Nusantara, and Sekolah Berkebun which will be included in the assessment of the Regional Development Awards (PPD) for Regency/City at the Central Java Province level. In carrying out this innovation, the Semarang City Government also encourages the involvement of all levels of society, especially women's groups and children through the curriculum in schools. This urban farming can support nutritional improvements for stunted children in the City of Semarang. As is known, the City of Semarang has succeeded in scoring a hat trick as the first best city in the Regional Development Awards or PPD for 3 consecutive years (2019, 2020, 2021) both at the Central Java Province and national levels. One of the activities that can support the urban farming program is the availability of green houses for plant nurseries in the RT, RW, and sub-district sectors. The construction of green houses for nurseries is very important for the community, especially residents of RT 06, Meteseh Village, so that they can produce plant seeds independently and can carry out planting activities or movements carried out by the Semarang city government